Clinical efficacy of collateral circulation in the evaluation of endovascular treatment for acute internal carotid artery occlusion. Issue 4 (April 2019) - Chen, Wang; Song, Xiaojie; Tian, Dachen; Sun, Hongyang; Zhang, Lijun; Hui, Xin; Ip, Bonaventure YM.; Wang, Xianjun
Abstract: Objectives: Despite successful recanalization, there remain many patients suffering bad outcome after endovascular treatment, especially for occlusion at the distal portion of internal carotid artery. The goal of the current study was to investigate the value of collateral circulation in predicting malignant events after endovascular treatment in acute ischemic stroke-terminal internal carotid artery (AIS-TICA) patients. Methods: The records of forty-one patients with AIS-TICA as confirmed by digital subtraction angiography and subjected to mechanical thrombectomy were reviewed. On the basis of the collateral circulation grading system (ACG) from the American Society of Interventional and Therapeutic Neuroradiology/American Society of Interventional Radiology (ASITN/SIR), class of leptomeningeal compensation were evaluated as grade 0 to 4. Factors for malignant events were evaluated by retrospectively univariate analysis. Moreover, analysis of correlation was performed between collateral circulation and malignant events. Malignant events were defined as a malignant middle cerebral artery infarction or parenchymal hemorrhage 2. Results: Of the 41 subjects, 13 (31.71%) had postoperative malignant events. Though 36 (87.80%) of the patients had a complete recanalization, only 17 patients (41.46%) showed good outcomes with modified Rankin score≤2 at 3 months. 9 (21.95%) deaths occurred in the hospital. Besides, patients in the malignant group had significantly higher scores on the National Institute of Health stroke scale (P = 0.032) and lower anterior circulation compensation (P = 0.000). Furthermore, correlation analysis showed that probability of malignant events was negatively correlated with anterior circulation compensation (rs = -0.534, P = 0.000). Conclusions: The leptomeningeal compensation of anterior circulation can be predicted whether a malignant event will occur after endovascular treatment in AIS-TICA patients. The probability of malignant events is significantly increased if the anterior circulation collateral compensation score is 0–1.